Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1086/507488
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Loss-of-Function Mutations in PCSK9 and Identification of a Compound Heterozygote

Abstract: Elevated levels of circulating low-density lipoprotein cholesterol (LDL-C) play a central role in the development of atherosclerosis. Mutations in proprotein convertase subtilisin/kexin type 9 (PCSK9) that are associated with lower plasma levels of LDL-C confer protection from coronary heart disease. Here, we show that four severe loss-of-function mutations prevent the secretion of PCSK9 by disrupting synthesis or trafficking of the protein. In contrast to recombinant wild-type PCSK9, which was secreted from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
401
0
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 595 publications
(440 citation statements)
references
References 28 publications
12
401
0
10
Order By: Relevance
“…The predicted translation product of this mRNA is a short peptide of 81 amino acids devoid of function, which most likely is not produced because of the rapid degradation of the corresponding mRNA (nonsense-mediated mRNA decay) as demonstrated for the nonsense mutation Y142X found in blacks. 26 The plasma levels of LDL-C and apoB in the proband heterozygous for Ala68fsLeu82X was similar to that found in our FHBL patients heterozygous for APOB gene mutations and in APOB"negative" FHBL subjects. However, the analysis of available family members revealed that in the 2 other adult carriers of the mutation (the father and paternal aunt of the proband) the level of plasma LDL-C and apoB were reduced to a much lesser extent as compared with the proband.…”
Section: Pcsk9 Is a Plausible Candidate Gene In Fhblsupporting
confidence: 84%
“…The predicted translation product of this mRNA is a short peptide of 81 amino acids devoid of function, which most likely is not produced because of the rapid degradation of the corresponding mRNA (nonsense-mediated mRNA decay) as demonstrated for the nonsense mutation Y142X found in blacks. 26 The plasma levels of LDL-C and apoB in the proband heterozygous for Ala68fsLeu82X was similar to that found in our FHBL patients heterozygous for APOB gene mutations and in APOB"negative" FHBL subjects. However, the analysis of available family members revealed that in the 2 other adult carriers of the mutation (the father and paternal aunt of the proband) the level of plasma LDL-C and apoB were reduced to a much lesser extent as compared with the proband.…”
Section: Pcsk9 Is a Plausible Candidate Gene In Fhblsupporting
confidence: 84%
“…She had no immunodetectable circulating PCSK9. This 32-year-old African American woman with an LDL-C level of only 14 mg/dl, was apparently healthy, fertile, normotensive, with grossly normal hepatic, neuronal, and renal function tests [Zhao et al, 2006;Horton et al, 2007]. In one Sicilian hypobetalipoproteinemia kindred, a deletion in exon 1 (c.202delG) was found, which causes a frameshift in mRNA leading to a premature stop codon (p.A68fsL82X) [Fasano et al, 2007].…”
Section: Hypobetalipoproteinemia In Some Pcsk9 Loss-offunction Carriersmentioning
confidence: 99%
“…A woman originating from Zimbabwe, homozygote for p.C679X was reported by Hooper et al [2007] with very low LDL-C (15 mg/dl). Furthermore, Zhao et al [2006] reported a compound heterozygote for the p.Y142X mutation and an inframe 3-bp deletion (c.290_292delGCC) that deletes an arginine at codon 97. She had no immunodetectable circulating PCSK9.…”
Section: Hypobetalipoproteinemia In Some Pcsk9 Loss-offunction Carriersmentioning
confidence: 99%
“…Conversely, loss‐of‐function PCSK9 mutations are associated with lower serum LDL‐C levels, lower lifelong exposure of vascular structures to LDL, and marked reduction of risk of coronary heart disease 27, 28, 29. Moreover, healthy subjects with severe loss of PCSK9 function have been shown to have serum LDL‐C concentrations as low as 14 mg/dL without apparent adverse health effects 28, 30…”
Section: Mechanism Of Action Of Pcsk9 Inhibitorsmentioning
confidence: 99%